Hubungan Latihan Pull Up Terhadap Kemampuan Panjat Tebing Kategori Lead Pada Atlet Pemula Klub Bunda84 Kabupaten Kepahiang - Aditia, Aditia (Educative Sportive, 2025)
This study aims to determine whether there is a relationship between Pull Up Training and Lead Category Rock Climbing Ability in Beginner Athletes of the Bunda84 Club, Kepahiang Regency. This type of research is correlation with the test method with a sample size of 13 students. The results of research on the Relationship of Pull Up Exercise to Lead Category Rock Climbing Ability in Beginner Athletes of the Bunda84 Club, Kepahiang Regency there is a relationship with the decision to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha). With the pull up test results being in the sufficient category with an average of 22.8 and in the rock climbing variable in the good category, namely with an average of 15.1 and who obtained the test norm in the good category. The correlation test was conducted to determine whether there was a relationship between Pull Up Training and Lead Category Rock Climbing Ability in Beginner Athletes of the Bunda84 Club, Kepahiang Regency. This correlation test uses the pearson product moment formula with the level of relationship being in the good category, namely 0.85. the results of the homogeneity test get the results of Fhitung is 1.66 and Ftabel is 2.12. Means Fhitung 1.66 < than Ftabel 2.12 then the distribution data Homogen. While the relationship between Pull Up Training and Lead Category Rock Climbing Ability in Beginner Athletes of the Bunda84 Club, Kepahiang Regency is 0.85 in a good category position.